Support, not blame: safe partner disclosure among women diagnosed with HIV late in pregnancy in South Africa and Uganda - Adelline Twimukye; Yussif Alhassan; Beate Ringwald; Thokozile Malaba; Landon Myer; Catriona Waitt; Mohammed Lamorde; Helen Reynolds; Saye Khoo; Miriam Taegtmeyer (AIDS Research and Therapy, 2024)
Abstract Background HIV partner disclosure rates remain low among pregnant women living with HIV in many African countries despite potential benefits for women and their families. Partner disclosure can trigger negative responses like blame, violence, and separation. Women diagnosed with HIV late in pregnancy have limited time to prepare for partner disclosure. We sought to understand challenges around partner disclosure and non-disclosure faced by women diagnosed with HIV late in pregnancy in South Africa and Uganda and to explore pathways to safe partner disclosure. Methods We conducted in-depth interviews and focus group discussions with pregnant women and lactating mothers living with HIV (n = 109), disaggregated by antenatal care (ANC) initiation before and after 20 weeks of gestation, male partners (n = 87), and health workers (n = 53). All participants were recruited from DolPHIN2 trial sites in Kampala (Uganda) and Gugulethu (South Africa). Topic guides explored barriers to partner disclosure, effects of non-disclosure, strategies for safe disclosure. Using the framework analysis approach, we coded and summarised data based on a socio-ecological model, topic guides, and emerging issues from the data. Data was analysed in NVivo software. Results Our findings illustrate pregnant women who initiate ANC late experience many difficulties which are compounded by the late HIV diagnosis. Various individual, interpersonal, community, and health system factors complicate partner disclosure among these women. They postpone or decide against partner disclosure mainly for own and baby’s safety. Women experience stress and poor mental health because of non-disclosure while demonstrating agency and resilience. We found many similarities and some differences around preferred approaches to safe partner disclosure among female and male participants across countries. Women and male partners preferred healthcare workers to assist with disclosure by identifying the ‘right’ time to disclose, mentoring women to enhance their confidence and communication skills, and providing professional mediation for partner disclosure and couple testing. Increasing the number of counsellors and training them on safe partner disclosure was deemed necessary for strengthening local health services to improve safe partner disclosure. Conclusion HIV diagnosis late in pregnancy amplifies existing difficulties among pregnant women. Late ANC initiation is an indicator for the likelihood that a pregnant woman is highly vulnerable and needs safeguarding. Respective health programmes should be prepared to offer women initiating ANC late in pregnancy additional support and referral to complementary programmes to achieve safe partner disclosure and good health.